2005
DOI: 10.1001/archneur.62.9.1393
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cortical Atrophy in Subgroups of Mild Cognitive Impairment

Abstract: To compare gray matter brain volumes in patients diagnosed with subtypes of mild cognitive impairment (MCI) (those with a focal amnestic disorder and those with more diffuse cognitive dysfunction) with those of elderly controls. Design: Magnetic resonance imaging volumetric study of MCI subgroups (MCI-amnestic [MCI-A], and MCImultiple cognitive domain [MCI-MCD]) using a whole brain voxel-based analysis. Setting: Referral dementia clinic. Patients: Thirty-seven patients with MCI (age range, 49-85 years; MCI-A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
130
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 24 publications
23
130
2
8
Order By: Relevance
“…The degree of memory impairment in the two subtypes did not differ. These and other results (Bell-McGinty et al, 2005) suggest that primary and secondary auditory cortices in the temporal lobe that generate the P50 component (LiegeoisChauvel et al, 1994;Reite et al, 1988) become involved as MCI progresses from isolated memory deficits (singledomain MCI) to additional cognitive dysfunctions involving language functions (multiple-domain MCI).…”
Section: Introductionmentioning
confidence: 80%
“…The degree of memory impairment in the two subtypes did not differ. These and other results (Bell-McGinty et al, 2005) suggest that primary and secondary auditory cortices in the temporal lobe that generate the P50 component (LiegeoisChauvel et al, 1994;Reite et al, 1988) become involved as MCI progresses from isolated memory deficits (singledomain MCI) to additional cognitive dysfunctions involving language functions (multiple-domain MCI).…”
Section: Introductionmentioning
confidence: 80%
“…Neuroimaging studies show structural [4][5][6][7] and functional features [8] in patients with aMCI that are intermediate between those of healthy subjects and AD patients, consistent with neuropathologic evidence of transitional pathologic findings [9,10]. Furthermore, magnetic resonance imaging studies have shown atrophy in not only medial temporal structures but also the inferior and lateral temporal lobes, the cingulate gyrus, and the parietal and frontal lobes, depending on the stage of disease [11][12][13][14]. Some of the earliest changes occur in the anterior medial temporal lobe and fusiform gyrus, as much as 3 years before the diagnosis of AD [15].…”
Section: Introductionmentioning
confidence: 90%
“…While these psychotherapies have been shown to be effective in the treatment of LLD, as with medication treatments, a significant portion of individuals receiving treatment do not respond to these interventions (14, 23). Given the cognitive demands of psychotherapy and known associations between cognitive deficits and cortical atrophy in older adults (25, 26), as well as the impact of cortical atrophy on antidepressant treatment response (18, 27), there is compelling evidence to suggest that cortical atrophy may have a deleterious impact on psychotherapy treatment outcomes. Further, given recent findings of prominent reductions in right hemisphere cortical thickness associated with familial risk of depression; indices of cortical thickness may be a particularly sensitive phenotypic marker of psychotherapy treatment response in older adults.…”
Section: Introductionmentioning
confidence: 99%